Bilateral Primary Angiosarcoma of the Breast - P. Keshav; Shruti S. Hegde (Case Reports in Surgery)
Primary breast sarcomas are very rare entities, accounting for 0.04% of all malignant neoplasms. Angiosarcoma of breast is infrequent and is an endothelial malignant tumor with bad prognosis because of the frequency of metastasis and recurrence. We present a case of a 30-year-old female who presented with an ulcerated left breast lesion which on further workup revealed to be a primary angiosarcoma of breast with metastasis to right breast.